Analisis Kesiapan Guru PAI Terhadap Adopsi Artificial Intelligence dalam Pembelajaran Al-Quran: Tinjauan Technology Readiness Index - Zulfikar, Muhammad; Supriadi, Udin; Surahman, Cucu (Fakultas Agama Islam, 2026)
The integration of Artificial Intelligence (AI) in Islamic Religious Education (PAI) offers efficiency but sparks theological debates on scholarly authority. This study analyzes the readiness of PAI teachers for AI adoption in Al-Qur'an learning using the Technology Readiness Index (TRI). Employing a phenomenological qualitative approach, data were collected through in-depth interviews with five teachers across generations (Gen-X and Gen-Z). Reflexive thematic analysis mapped the dimensions of Optimism, Innovativeness, Discomfort, and Insecurity. The findings reveal a